McCain Chronicles : The Covenant - Book 1 - Rundell, B.N. (Thorndike, Maine : Center Point Large Print, 2024)
"It was a time of uncertainty in the infancy of the growing nation. The Wild West was open and beckoning to displaced men and families, and many chose to travel to the unsettled frontier, dreaming of new homes, land, and even riches. But few reckoned on those that had lived in those lands for centuries, the native peoples: Blackfoot, Crow, Sioux, and more. Elijah McCain, fresh from the Union army -- where he had attained the rank of Lieutenant Colonel with the Mounted Rifles, the cavalry unit under General Sherman -- returned home to find his wife on her deathbed, but pleading for her twin sons. She elicited a promise, a covenant, from her husband, "Find my boys, bring them home." And Eli made that covenant. Holding her hand as she slipped from life, he promised he would bring her sons, his stepsons, home one way or the other. But would that promise be the undoing of dreams, lives, and more? Her final wish has become his lifes mission . . ."- -
Keywords: Promises -- Fiction; Quests (Expeditions) -- Fiction; Missing persons -- Fiction; Frontier and pioneer life -- United States; Fiction; Widowers -- Fiction; Indians of North America -- Fiction; United States -- History -- Civil War, 1861-1865; Veterans; Fiction; West (U.S.) -- Fiction; Western fiction; Large print books